The role of instruction preference in analogy learning: Brain activity and motor performance. (March 2020) - van Duijn, Tina; Crocket, Hamish; Masters, Rich S.W.
Abstract: This study examined the role of verbal instruction preference when learning motor skills by analogy. During skill learning, analogies are a useful tool for providing knowledge about how to move. It has been argued that analogy instructions reduce reliance on verbal information processes during motor planning, compared to traditional forms of instruction (i.e., explicit rules about how to move). This may be reflected by reduced verbal activity in the brain, measured by EEG alpha power at the temporal region, as well as reduced verbal-motor cross-communication (EEG T7-Fz coherence) during the preparation phase of a movement. Preference for using verbal or visual instructions is likely to influence the efficacy of analogy instructions. This study investigated whether preference for verbal instructions was related to a) changes in performance and b) changes in verbal-cognitive information processing during performance of an adapted basketball task after instruction by analogy. Basketball novices with a high preference for verbal instructions (n = 15) showed significantly decreased activation of verbal brain regions when they used the analogy (high-alpha power), but their performance remained stable. Novices with a low preference for verbal instructions (n = 13) did not show a significant decrease in activation of verbal regions, and their performance deteriorated significantly after introduction of the analogy instruction. It is likely that both cognitive and performance changes after analogy instruction depend on personal aspects of information processing, such as verbal preference. Highlights: We investigated performance and information processing before and after motor learning of a basketball task by analogy. People with a high verbal preference showed a decrease in activation of verbal brain regions (EEG high-alpha power) when using the analogy. In people with a high verbal preference, motor performance remained stable, while it deteriorated in other participants. It is likely that cognitive and performance changes after analogy instruction are related to instruction preference.